Pengaruh Media Blog Terhadap Kemampuan Menulis Teks Cerpen pada Siswa Kelas Xl MAS Al-Washliyah Tebing Tinggi Tahun Pembelajaran 2022-2023 - Nurhayati, Nurhayati; Nirmawan, Nirmawan (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study examines the impact of using blog media on students' short story writing skills in class XI at Mas Al-Washliyah Tebing Tinggi during the 2022-2023 academic year. The quantitative descriptive method was employed, with a total sample size of 32 students from both experimental and control classes. The data was collected through pretest and posttest essays. Posttest scores in the experimental class showed 12% in the very good category, 75% in the good category, 13% in the sufficient category, and 0% in the less and very less categories, with an average score of 75.25. On the other hand, the control class demonstrated 38% in the good category, 38% in the sufficient category, 19% in the less category, and 5% in the very less category, with an average score of 64.87. The results indicated that the experimental class, which utilized blog media, outperformed the control class that used conventional methods. Therefore, it can be concluded that blog media positively influences learning outcomes in writing short stories.